The ecological effect of Acacia saligna in a sand plain fynbos ecosystem of the Western Cape, South Africa - Van den Berckt, Tom (Stellenbosch : Stellenbosch University, 2012)
Thesis (MScFor)--Stellenbosch University, 2002.